In vitro effect of nicorandil on the carbachol-induced contraction of the lower esophageal sphincter of the rat - Tomonori Shimbo; Takeshi Adachi; Susumu Fujisawa; Mai Hongoh; Takayoshi Ohba; Kyoichi Ono (Elsevier, 2016)
The lower esophageal sphincter (LES) is a specialized region of the esophageal smooth muscle that allows the passage of a swallowed bolus into the stomach. Nitric oxide (NO) plays a major role in LES relaxation. Nicorandil possesses dual properties of a NO donor and an ATP-sensitive potassium channel (KATP channel) agonist, and is expected to reduce LES tone. This study investigated the mechanisms underlying the effects of nicorandil on the LES. Rat LES tissues were placed in an organ bath, and activities were recorded using an isometric force transducer. Carbachol-induced LES contraction was significantly inhibited by KATP channel agonists in a concentration-dependent manner; pinacidil >> nicorandil ≈ diazoxide. Nicorandil-induced relaxation of the LES was prevented by pretreatment with glibenclamide, whereas NG-nitro-l-arginine methyl ester (l-NAME), 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ) and iberiotoxin were ineffective at preventing nicorandil-induced LES relaxation. Furthermore, nicorandil did not affect high K+-induced LES contraction. Reverse-transcription polymerase chain reaction analysis and immunohistochemistry revealed expression of KCNJ8 (Kir6.1), KCNJ11 (Kir6.2), ABCC8 (SUR1) and ABCC9 (SUR2) subunits of the KATP channel in the rat lower esophagus. These findings indicate that nicorandil causes LES relaxation chiefly by activating the KATP channel, and that it may provide an additional pharmacological tool for the treatment of spastic esophageal motility disorders.